Post-lockdown clinics: 'Just when you thought it was safe to go back in the water…'. Issue 6 (June 2020) - Howard, Nick; Tromans, Cindy
Abstract : Nick Howard and Dr Cindy Tromans offer some thoughts on the safe reintroduction of eye care clinical services.